The Influence of Halal Certification, Halal Awareness, and Promotion on Purchase Intention of Se'Indonesian Products Among Muslim Consumers in Surabaya City - Andi Riyadi; Irfan Ramis (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The low number of halal certifications in Indonesia, reaching only 6,4 million out of 30 million culinary MSMEs, raises consumer doubts and decreases purchase intentions. This issue is compounded by the low level of halal awareness among the public, particularly the youth who lack understanding of the halal concept, as well as ineffective social media promotions that merely copy trends without clear objectives, leading to a decline in buying interest. This study aims to analyze the influence of halal certification, halal awareness, and promotion on the purchase intention of Se'Indonesia products among Muslim consumers in Surabaya. A quantitative research method was employed, utilizing primary data obtained from an online questionnaire distributed to 120 respondents selected via purposive sampling, and analyzed using multiple linear regression. The results indicate that halal certification, halal awareness, and promotion have a positive and significant effect on purchase intention, both partially and simultaneously, with a combined contribution of 81.6%. This research can serve as a reference for policies or decisions and provide insights for related parties.